Development of Alternative Green Sample Preparation Techniques - Gionfriddo, Emanuela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue of Separations, "Development of Alternative Green Sample Preparation Techniques", provides an overview on recent trends in green sample preparation. This Special Issue of Separations collates 11 impressive contributions that describe the state-of-the-art in the development of green extraction technologies, from green materials for microextraction to the development of new sampling devices geometries for enhanced extraction efficiency and analysis throughput.